Routes to social prescribing outside National Health Service (NHS) structures: a systematic map - Kerryn Husk; Stephanie Tierney; Lucy Gavens; Emma Hazeldine; Sophie Westwood; Mohammad Hassannezhad (BMJ Public Health)
Objectives Social prescribing, linking to community-based interventions to support individuals’ health and well-being, has become established across social medicine in the UK. Currently, most of the evidence and knowledge about how social prescribing pathways’ function focuses on primary care, and we know less about how social prescribing operates outside of these structures. This review explored the evidence concerning non-health service delivered social prescribing with a view to developing guidance that would support social prescribing pathways that function outside of the health service framework.Design This paper reports a systematic mapping review of evidence concerning how community-based social prescribing pathways were delivered, exploring what these looked like, what needed to be in place for these to function, what outcomes were measured and how could non-health service pathways be supported to deliver these outcomes. The review searched database and grey sources and synthesised findings relating to how social prescribing pathways’ function.Setting Community settings, outside of formal National Health Service (NHS) structures without statutory service input.Participants All participants that experienced pathways were included; no limits were applied.Interventions Non-NHS social prescribing pathways that included the core components of social prescribing.Main outcome measures Rich descriptions of functions of pathways.Results This mapping review included 17 studies. The synthesis indicated that NHS and non-NHS social prescribing pathways are intertwined and mutually reliant, such that it was neither sensible nor valuable to view them as separate.Conclusions Our review provides further evidence for social prescribing as a concept, variable across all components, rather than a single, coherent model. While there exists a ‘core’ health service pathway, we suggest that further work should be done with those delivering services to understand the roles and functions that contribute but may not presently be funded.